Scoping Review : Perspektif Kesejahteraan Karyawan UMKM - Suryo Prakoso, Agung; Sopiah, Sopiah (Jurnal Ilmu Multidisiplin, 2023)
Employee welfare is present as an important element for the sustainability and development of an SME. Employees who are well cared for physically and mentally will be able to feel comfortable and prosperous in the workplace. The purpose of this research is to find out more about how the welfare of employees in an SME can affect the sustainability of the SME . This scoping review aims to examine the literature regarding the most relevant and significant aspects of employee welfare, as well as the methods used in related research. This scoping review aims to examine the literature regarding the most relevant and significant aspects of employee welfare, as well as the methods used in related research. This study searches for articles from several databases published between 2010 and 2021. The results show that employee well-being includes four dimensions, namely physical, psychological, social, and work environment. Several methods used in research include surveys, interviews, and observation. The results of the study show that the welfare of employees in a work environment will have a positive effect on various aspects, all of which will lead to the sustainability of SMEs. High morale from employees will be created if the employee is prosperous in the work being carried out.